(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study intends to investigate the benefit of applying modern method and its effects on learners’ learning of English language. Using technology in teaching and learning has developed and used recently which leads to renew methods of teaching by educational directorates and teachers as well. Blended teaching is the most technique which is commonly used nowadays . Since the quick technological progression has emerged, schools try to teach the English to help the students to understand it and equip them with skills to go long and use it in everyday life and communication on internet. Iraqi EFL learners have some problem in understanding and getting English lessons by traditional methods of teaching used by their teachers. To develop students’ skills, teachers have to vary their techniques as well as the methods in teaching the language. This study tries to supply an overview of the effect of utilizing blended method on the students’ achievement in learning the English through using blended learning strategy.